Microstructural analysis and mechanical properties characterization in a set of commercial nodular cast iron - Fernandes, Daniel de Oliveira (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade UnB Gama, Programa de Pós-Graduação em Integridade de Materiais da Engenharia, 2022.